SAMHD1 deficiency enhances macrophage-mediated clearance of Salmonella Typhimurium via NF-κB activation in zebrafish - Martínez-López, Alicia; Tyrkalska, Sylwia D.; Martínez-Morcillo, Francisco J.; Abenza-Olmos, Constantino; Lozano-Gil, Juan M.; Candel, Sergio; Mulero, Victoriano; García-Moreno, Diana (Frontiers in Immunology, 2025)
IntroductionMutations in the gene encoding the protein containing the sterile alpha motif and the HD domain (SAMHD1) have been implicated in the occurrence of type I interferonopathies. SAMHD1 is also involved in blocking the replication of retroviruses and certain DNA viruses by reducing the intracellular amount of deoxynucleotide triphosphates (dNTPs). It has also been suggested that SAMHD1 negatively regulates interferon (IFN) and the inflammatory responses to viral infections; however, the functions and mechanisms of SAMHD1 in modulating innate immunity are still under study.MethodsIn our laboratory, we have generated Samhd1-deficient zebrafish larvae using CRISPR-Cas9 and studied its role in the activation of nuclear factor kappa B (NF-κB) and the induction of type I IFN (IFN-I).ResultsIt was shown that Samhd1 deficiency results in the overactivation of the IFN-I response, assayed as the increased transcript levels of the Interferon Stimulated Genes (ISGs), but only if the larvae were stimulated with suboptimal doses of IFN-I. However, Samhd1-deficient larvae showed robust spontaneous activation of NF-κB, which led to increased larval resistance to Salmonella enterica serovar Typhimurium (STM) infection. Genetic experiments further showed that the activation of NF-κB in macrophages mediated the resistance of Samhd1-deficient larvae against STM.DiscussionThese findings highlight the evolutionary conserved functions of SAMHD1 in the negative regulation of the inflammatory response of vertebrates and reveal, for the first time, a critical role for SAMHD1 in the regulation of NF-κB in macrophages to clear intracellular bacterial infection.